Noise exposure, hearing loss and cognitive impairment: a cross-sectional study based on an occupational health surveillance cohort in China - Huang, Lei; Li, Linjuan; Wang, Juan; Zhang, Shushan; Wu, Huiyi; Lan, Yajia; Li, Junying; Zhang, Yang (Frontiers in Public Health, 2025)
BackgroundHigh-intensity noise is associated with noise-induced hearing loss (NIHL). There is also evidence that noise exposure is related to cognitive impairment. This research aimed to analyze the associations and potential pathways of cumulative noise exposure (CNE), hearing loss and cognitive impairment.MethodsA total of 560 research subjects were included in this research from May 2021 to April 2022 in western China. The demographic features, occupational features, and CNE were investigated and examined. Hearing loss was evaluated according to the National standard GB/T 7583–1987 of China. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to assess cognitive function. Structural equation modeling (SEM) was used to analyze the potential pathways and specific effect sizes of CNE, hearing loss and cognitive impairment.ResultsThe mean age of the research subjects was 34.3 (SD, 9.89). Men accounted for 96.4% (540/560) and women accounted for 3.6% (20/560). A total of 62.3% (349/560) held a college degree or above. The regression analysis showed that high dose CNE was related to MMSE (β = −1.069 (−1.539, −0.600)) and MoCA (β = −1.040 (−1.726, −0.355)) scores. The monaural threshold weighted value of the right ear (MTWVR) greater than 40 dB was associated with both MMSE (β = −1.183 (−2.033, −0.333)) and MoCA (β = −1.420 (−2.647, −0.193)) scores. The monaural threshold weighted value of the left ear (MTWVL) greater than 40 dB was also associated with MMSE (β = −1.540 (−2.389, −0.690)) and MoCA (β = −1.685 (−2.915, −0.456)) scores. The SEM result (Model C) showed that the standard effect of CNE- hearing loss path, CNE-MMSE path, and hearing loss-MMSE path were 0.142 (p < 0.001), −0.151 (p < 0.001), and −0.030 (p = 0.376). The Model D showed that the standard effect of CNE- hearing loss path, CNE- MoCA path, and hearing loss- MoCA path were 0.143 (p < 0.001), −0.048 (p = 0.267), and − 0.050 (p = 0.047). The CNE had only a direct effect on the MMSE score. Conversely, the CNE had only an indirect effect on the MoCA score, while hearing loss was borderline associated with MoCA. The total effects of CNE on MMSE and MoCA scores were −0.151 and −0.007, respectively.ConclusionJob-related noise exposure is not only associated with NIHL but also with early cognitive impairment in occupational groups. However, there is not enough evidence indicating that NLHL mediates the associations.